Genealogy and literature - Quinby, Lee, 1946- (University of Minnesota Press, 1995)
Traditionalists insist that literature transcends culture. Others counter that it is subversive by nature. By challenging both claims, Genealogy and Literature reveals the importance of literature for understanding dominant and often violent power/knowledge relations within a given society.